Effects of Chlorella sp. Additions on the Changes of Visceral Mass and Proximate Contents of Shellfish - Clara Dhisa Sumunaring Ratna; Trijoko Trijoko (Jurnal Biologi Universitas Andalas, 2019)
Shellfish, called as kerang in Indonesia, contains animal protein that’s popular, making it as and important fisheries and marine commodity. Supported by the good taste and high nutrient content in it. Paphia undulata or Kerang  Batik, Peryglipta reticulata or Kerang Kemiri, Meretrix meretrix or Kerang Tahu, and Codakia tigerina or Kerang Madu, are consumption shells from northern coast of Java. To improve the quality of shellfish, Chlorella added as shellfish food preferences. It supported by the high nutrient content in Chlorella sp. Shellfish kept for 15 days in a basket with a sand substrate and drainage from sea. Therefore, the water quality had been controlled for the changed of salinity and water temperature. Parameters used to see the improvement shellfish quality is the color changes on visceral mass and the changes of proximate content (moisture, protein, fat, carbohydrate and ash). This study proves the color changes on visceral mass and proximate content. The color change occurs on the visceral mass and the gills. The changes of viscerall mass occurs on kerang batik from white greyish to yellow while the more clearly gills occurs on kerang madu and kemiri. Meanwhile, the change of proximate shown by the increasing of protein and moisture on all the spesies while on the otherside the decreasing of carbohydrate and ash, but the increasing of fat only occurs on kerang batik and kerang madu. The higher proximate changes occur on kerang madu, where the ammount of moisture at 71,43 ± 0,03 %, the protein at 16,55 ± 0,02 %, the fat at 1,35 ± 0,04 %, the carbohydrate at 2,9 ± 0,03 %, and the ash at 8,09 ± 0,04 %. The conclusion of this research are kerang madu has the higher positive influences by addition of Chlorella, shown by the increasing of proximate contents and the clearly of gills. Keywords : addision of Chlorella sp., changes of visceral mass, proximate, shellfish